Meningkatkan Daya Saing Kerupuk Kamang melalui Diferensiasi Produk dan Strategi Pemasaran Digital - Chairunnisya; Adisti, Adila; Ramadhani, Ratih; Mazelfi, Ihsani; Wellyalina (Program Studi Ekonomi Pembangunan, 2025)
Kerupuk Kamang Dua Saudara is one of the MSMEs that produces kamang crackers. However, sales are only made to middlemen without a logo and proper packaging, so it does not have competitive advantages. This community service aims to solve problems in three aspects, namely the production aspect (increasing the amount of production and the use of technology in the form of cassava grinding machines), the marketing aspect (use of social media), and the managerial aspect (discipline in SOP production and financial management). To solve the problems partners face, the approach can be categorized into a community service method based on integrated solutions through socialization, training, mentoring, and application of technology. Product innovation and digital marketing are important steps to increase business competitiveness. This community service positively impacts the UMKM Kerupuk Kamang Dua Saudara through increased production, digital marketing, and business management. Service to partners has succeeded in increasing production capacity by adding cassava grinding machines and developing three new product variants. In the marketing aspect, zipper packaging with a logo and active social media accounts for digital promotion have been created. From the managerial side, partners now have production SOPs, simple financial reports, and legal documents such as NIB and PIRT assistance. These results significantly increase partner efficiency, competitiveness, and market opportunities.